PENGEMBANGAN MEDIA PEMBELAJARAN BOLA BASKET BERBASIS VIDEO ANIMASI UNTUK SISWA SEKOLAH MENENGAH PERTAMA - Tania Ika Putri; Eka Supriatna; Fitriana Puspa Hidasari (Universitas Tanjungpura, 2019)
AbstractThis study aims to develop new innovations in the form of video-based animation learning media that can add effectiveness to the learning process, especially basketball material at the junior high school level. This research is research and development (R & D). This study uses the ADDIE development method with several steps, namely: analysis, design, development, implementation and evaluation. The subjects of the trial in this study were Pontianak 10 Public High School, Pontianak 24 Public Middle School and Sungai Raya 2 Public Middle School. The results of the study were DVD (Digital Versatile Disk) interactive learning that had been validated and tested. The results of the validation by material experts got the category